Acute and Chronic Toxicity of Mercury Exposure in Seafood and Human Populations near a Small-Scale Gold Mining Area - Sofia Sofia; Adi Heru Husodo; Eko Sugiharto (International Journal of Public Health Science (IJPHS), 2016)
Gold amalgamation processes using mercury were practiced in small scale gold mining activities in Krueng Sabee, Aceh Province. Seafood (fish, mollusc, shrimp) and human hair samples were collected to assess mercury concentrations.  Acute and chronic toxicity symptoms which arise among the populations were observed as well as personal protective equipment used by gold miners. The range of mercury concentrations varied among fish, shrimp, and molluscs. The highest mercury levels were recorded in fish Puntius latristriga (172.299 ± 10.626 µg/g wet wt.), followed by mollusc, Polymesoda caroliniana (160,032 ± 0,522 µg/g wet wt.), fish R.kanagurta (149 ±2,000 µg/g wet wt.), shrimp Penaeus monodon (116.975 ± 4.807 µg/g wet wt.).  The variation of mercury concentrations in hair samples of 72 respondents were detected from 5.7 µg/g to 88.1 µg/g. The most frequent acute and chronic intoxication symptoms documented were headache, muscle cramps, cough, and aphthous ulcers. Personal protective equipment which has correlation with high mercury levels in gold miners were respirator/mask, gloves, and apparel (p < 0.05). All seafood samples exceeded 0.5 µg Hg/g MoH Food and Drug Administrasion threshold level and hair samples over 10 µg/g as set by WHO tolerance limit.